LeishTec vaccination disrupts vertical transmission of Leishmania infantum. - Diogo G Valadares; Eric Kontowicz; Serena Tang; Angela Toepp; Adam Lima; Mandy Larson; Tara Grinnage-Pulley; Breanna Scorza; Danielle Pessoa-Pereira; Jacob Oleson; Christine Petersen (PLoS Neglected Tropical Diseases)
Zoonotic canine leishmaniosis, caused by Leishmania infantum, is a fatal disease worldwide in both humans and the reservoir host, dogs. The primary route of transmission is via sand fly bite. Vertical, transplacental, transmission of L. infantum to offspring has been shown to be critical for maintenance of infection in both endemic and non-endemic areas. In the United States, canine leishmaniosis (CanL) is enzootic within hunting dog populations. Previous work with US hunting dogs found that transplacental transmission of L. infantum occurs frequently with high infectivity. Dogs born to CanL infected mothers were almost fourteen times more likely to become positive for L. infantum over their lifetime. Globally, public health agencies control CanL through canine and human case detection and treatment, and in some cases dog culling and reducing vector populations. There is no specific strategy to control vertical transmission of CanL. A previous randomized field trial in US hunting dogs found that a Leishmania A2 protein, saponin-adjuvanted, vaccine (LeishTec) used as an immunotherapy, significantly reduced the risk of progression to clinically overt leishmaniasis by 30% in asymptomatic dogs. It is unknown whether maternal vaccination could inhibit infection risk in her offspring. We hypothesized that dogs born to infected and vaccinated dams would be less likely to test diagnostically positive via L. infantum specific kqPCR or serology compared to dogs born to infected unvaccinated mothers. A population of dogs born to L. infantum infected dams were evaluated to assess LeishTec vaccination to prevent transmission to offspring. Dogs born to unvaccinated, L. infantum infected, dams had higher mortality (12.50% vs 0.00%), higher likelihood of clinical disease (94.12% vs 59.00%) and were more likely to be diagnostically positive for CanL (22.22% vs 4.55%). Vaccination of dams already infected prior to pregnancy greatly reduced the risk of transplacental transmission of L. infantum. Incorporating vertical transmission prevention as a public health intervention in countries where Leishmania is endemic could aid in infection control.